THE EFFECT OF ORGANIZATIONAL COMMUNICATION AND TECHNOLOGY TRAINING ON THE PERFORMANCE OF THE ROLE OF JOB SATISFACTION AS AN INTERVENING VARIABLE IN JEMBER REGENCY TRANSPORTATION OFFICE EMPLOYEES - Ika Tyas Nurlina; Nurul Qomariah; Feti Fatimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze and explain the influence of organizational communication and technology training on employee performance, with job satisfaction as an intervening variable in the Jember Regency Transportation Office. The background of this research is based on the importance of the role of effective communication and mastery of technology in improving professionalism and quality of public services in the digital era. The research method used is a quantitative approach with an explanatory research type. The population in this study is all employees of the Jember Regency Transportation Office, with the number of samples determined using the Slovin formula. Data collection was carried out through the distribution of questionnaires, then analyzed using path analysis techniques with the help of the SmartPLS program. Overall, this study emphasizes that improving the quality of communication and directed technology training is an important strategy for the Jember Regency Transportation Office in creating a competent, service-oriented, and adaptive apparatus to the development of digital technology in supporting the implementation of professional and efficient public transportation